EXPANDING TAX EDUCATION: INSIGHTS FROM ACADEMIC PROFESSIONALS - Nor Azrina Mohd Yusof; Roshidah Safeei; Lee Chai Chuen (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Taxation serves as a primary revenue source for most developing countries. However, despite this reliance, many governments face similar challenges in tax collection. For example, Malaysia ranks fourth among Asian and Pacific nations for the lowest tax-to-GDP ratio. This is particularly surprising given that the self-assessment system (SAS) has been in place for over two decades, yet voluntary tax compliance remains low. Research indicates that Malaysian taxpayers still lack sufficient tax literacy. Therefore, this study aims to (i) assess the need for introducing tax education within non-accounting curriculum among academic professionals in non-accounting disciplines, (ii) evaluate the level of tax knowledge among these academic professionals, and (iii) identify their preferences regarding taxation topics if tax courses were integrated into their curriculum.In September 2021, an online survey was distributed to all non-accounting academicians across the Universiti Teknologi MARA (UiTM) system over a three-week period, yielding 358 responses, with 349 being suitable for data analysis. The results revealed that (i) the majority of respondents likely support the inclusion of tax courses in all faculties, (ii) 50.4% of respondents demonstrated a basic level of tax literacy, and (iii) the most preferred tax topics were real property gains tax, tax planning for small businesses, and small company taxation. Despite the long-standing implementation of Malaysia’s self-assessment system, 41.8% of respondents still had only a moderate understanding of tax matters. These findings suggest potential collaboration between the Malaysian Ministry of Higher Education and the Malaysian Inland Revenue Board to introduce tax education to non-accounting students at the tertiary level. However, given that the sample was limited to UiTM academicians from non-accounting fields, the results should be interpreted and generalized with caution.